Exploring the impact of virtual exchange in Virtual English as a lingua franca (VELF): Views on self-efficacy and motivation - Nicolaou, Anna; Sevilla-Pavón, Ana (My University, 2023)
While bilingual or e-tandem exchanges have been implemented in foreign language education for more than two decades with well-documented success, lately there is a growing interest in lingua franca virtual exchanges. Considering that English is a common lingua franca across the globe, today's graduates are required to be adept at using English as a lingua franca in their academic and professional careers. This applies in both in-person and online settings. In this context, lingua franca virtual exchanges provide a suitable approach for affording opportunities to university learners for realistic intercultural encounters, rendering them competent and confident in using the language. This paper explores the impact of a Virtual English as a lingua franca (VELF) exchange project on the student participants’ views of their self-efficacy as well as on their motivation to learn English. The study followed a mixed-methods approach with qualitative and quantitative data collection. The findings revolve around themes pertaining to the development of the participants’ self-efficacy levels, such as confidence in communicating with their foreign counterparts who speak their own version of English, and handling unforeseen circumstances that arise in online communication. Results also reveal significant differences in the participants’ motivation and value placed on several learning activities.